Screen Time and Emotional-Behavioral Problems in School-Aged Children: A Cross Sectional Study - Dauhan, Clarita Jolanda Glorya; Gannika, Lenny; Simanjuntak, Susi Roida (Genius Journal, 2025)
Background: The rapid development of digital technology has led to increased screen time among children, raising concerns about its potential impact on emotional and behavioral development. Excessive screen exposure is suspected to contribute to psychosocial issues in school-aged children. Objective: This study aims to analyze the relationship between screen time and emotional and behavioral problems in school-age children. Method: A cross-sectional quantitative design was employed. A total of 92 parents of students at a private elementary school in Tahuna, North Sulawesi, were selected using proportionate stratified random sampling. Data were collected using a validated screen time questionnaire and the Pediatric Symptom Checklist-17 (PSC-17). Statistical analysis was performed to assess the relationship between screen time and emotional and behavioral problems. Result: Findings showed that 83.7% of children had screen time exceeding WHO recommendations, and 84.8% exhibited signs of emotional and behavioral problems. A statistically significant relationship was found between excessive screen time and emotional and behavioral issues (p < 0.05). Conclusion: Excessive screen time is significantly associated with an increase in emotional and behavioral problems among school-aged children. Interventions aimed at monitoring and reducing screen exposure are strongly recommended to support children's psychosocial well-being.